Effect of Moderate-Intensity Aerobic Exercise on Selected Indicators of Mitochondrial Biogenesis in the Myocardial Tissue of Diabetic Male Wistar Rats - Sadegh Jafari; Farzad Nazem; Hesam Parsa (Journal of Mazandaran University of Medical Sciences)
Background and purpose: Impaired mitochondrial biogenesis in heart tissue is one of the contributing factors to the pathogenesis of type 2 diabetes mellitus (T2DM). Physical activity represents a non-pharmacological intervention for enhancing the mitochondrial biogenesis pathway. The present study aimed to investigate the effect of aerobic exercise on the expression of genes associated with key indicators of mitochondrial biogenesis in the heart tissue of diabetic rats. Methods & Materials: A laboratory-based experimental study was conducted on 32 male Wistar rats, randomly assigned to four groups: control, sham, diabetic, and intervention diabetic (with aerobic exercise for either 3 or 5 days per week). Diabetes was induced using streptozotocin (60 mg/kg). Exercise training was performed on a treadmill for 10 weeks (3 or 5 days per week, 30 to 55 minutes per day). Blood and heart tissue samples were collected for biochemical analyses and gene expression studies using qRT-PCR, focusing on PGC-1α, NRF1, NRF2, and TFAM genes. Data were analyzed using one-way analysis of variance (ANOVA). Results: The expression of PGC-1α and NRF2 genes in the heart tissue of the sham diabetic group was reduced compared to the control group, accompanied by a significant increase in fasting blood sugar (FBS) and HbA1c levels (P<0.05). However, the expression of NRF1 and TFAM genes did not show a significant difference between these groups. The effect of aerobic exercise on diabetic rats demonstrated that, in the intervention group with three alternating days of exercise per week, the expression levels of PGC-1α, NRF2, and TFAM genes in cardiac tissue significantly increased compared to the sham group (P<0.05). In contrast, no significant difference was observed in the levels of these genes in the intervention group with five days of exercise per week, compared to the sham group. Furthermore, NRF1 gene expression did not differ significantly in any of the training groups compared to the sham group (P>0.05). Conclusion: Moderate-intensity aerobic exercise performed three days per week plays a beneficial role in enhancing the mitochondrial biogenesis pathway in the myocardium of diabetic rats by upregulating the expression of PGC-1α, NRF2, and TFAM genes in heart tissue.